Targeting Epstein-Barr Virus in Nasopharyngeal Carcinoma - Hau, Pok Man; Lung, Hong Lok; Wu, Man; Tsang, Chi Man; Wong, Ka-Leung; Mak, Nai Ki; Lo, Kwok Wai (Frontiers in Oncology, 2020)
Nasopharyngeal carcinoma (NPC) is consistently associated with EBV infection in the endemic regions including South China and Southeast Asia. The high mortality rates of NPC patients with advance and recurrent diseases highlight the urgent need for effective treatment interventions. While recent genomic studies have revealed few druggable targets, the unique interaction between the EBV infection and host cells in NPC strongly implies that targeting EBV is an efficient approach to cure this virus-associated cancer. The continued presence of an episomal EBV genome and the requirement of multiple viral latent gene products in malignant transformation are key features of EBV-associated NPC. By exploiting these unique features, multiple translational studies for developing pharmaceutical agents and therapeutic strategies targeting EBV latent proteins and inducing lytic reactivation in NPC have been conducted. Among the EBV latent proteins, inhibitors for EBNA1 have been intensively explored because of its essential roles in maintaining EBV latency and viral genome replication in NPC cells. Recent advances in chemical bioengineering enforces the development of therapeutic agents targeting the critical functional regions of EBNA1. Promising therapeutic effects of those specific EBNA1 inhibitory compounds have been shown in EBV-positive NPC tumors. The efficacy of multiple classes of EBV lytic inducers for NPC cytolytic therapy has also been investigated for decades. However, these compounds showed various efficiencies in lytic induction among different EBV-positive NPC models in a cell-context dependent manner. In each tumor, NPC cells might evolve and acquire somatic changes to ensure EBV latency during cancer progression. The poor understanding on the cellular mechanisms regulating EBV latency to lytic switch in NPC cells limits the clinical application of EBV cytolytic treatment. The potential approaches for improvement of those EBV targeting strategies are discussed in this review.